2016
DOI: 10.1017/s0022050716000826
|View full text |Cite
|
Sign up to set email alerts
|

People, Plagues, and Prices in the Roman World: The Evidence from Egypt

Abstract: The papyri of Roman Egypt provide some of the most important quantifiable data from a first-millennium economy. This paper builds a new dataset of wheat prices, land prices, rents, and wages over the entire period of Roman control in Egypt. Movements in both nominal and real prices over these centuries suggest periods of intensive and extensive economic growth as well as contraction. Across a timeframe that covers several severe mortality shocks, demographic changes appear to be an important, but by no means t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(27 citation statements)
references
References 47 publications
0
16
0
2
Order By: Relevance
“…They even threw them half dead into the roads and treated unburied corpses like refuse in hope of avoiding the plague of death, which, for all their efforts, was difficult to escape. (Maier, 1999, p. 240) Although it could be argued that Dionysius had a biased view of Christian charity, Harper (2016) makes the point that it would be difficult to exaggerate or fabricate an experience that his audience was experiencing first hand.…”
Section: Cases Of Prestige-driven Dynamics In Religious Historymentioning
confidence: 99%
“…They even threw them half dead into the roads and treated unburied corpses like refuse in hope of avoiding the plague of death, which, for all their efforts, was difficult to escape. (Maier, 1999, p. 240) Although it could be argued that Dionysius had a biased view of Christian charity, Harper (2016) makes the point that it would be difficult to exaggerate or fabricate an experience that his audience was experiencing first hand.…”
Section: Cases Of Prestige-driven Dynamics In Religious Historymentioning
confidence: 99%
“…49 ; Elliott (2016). 50 Harper (2016a). 51 The pestilence in Edessa is also of particular importance potentially, since it provides strong observational evidence for epidemic smallpox in the 5th c. Medical sources from the 7th to 9th c.-from Alexandria to Iraq, Persia and Mortality estimates for the Antonine Plague have varied from as little as 2% of the population to as much as 25-30%, although I have argued for something in the realm of 10% of the empire's population as a whole.…”
Section: Ecology Environment Evolutionmentioning
confidence: 99%
“…Now, Scheidel's Malthusian model is among the most serious and coherent presentations of the Roman economy in the recent literature, but it should be obvious even to non‐specialists that my conclusions depart from it. In rebuilding the wage, price, and rent data from the ground up, I found that the evidence indicates intensive growth in Roman Egypt down to the Antonine plague (Harper, ). In fact, the hypothesis of intensive growth in the Roman Empire is utterly central to the argument in The Fate of Rome and developed in opposition to the Malthusian paradigm, so these are not just finer points misunderstood by the group.…”
Section: What Can We Know About the Roman Pandemics?mentioning
confidence: 99%
“…In fact, the hypothesis of intensive growth in the Roman Empire is utterly central to the argument in The Fate of Rome and developed in opposition to the Malthusian paradigm, so these are not just finer points misunderstood by the group. Moreover, the labor‐intensive project of reconstructing the rent data to calibrate for fallowing was undertaken precisely in order to answer the legitimate concerns of Bagnall (Harper, , p. 812). The confident accusations of the group stand in contrast to their incomplete grasp of the issues, and the Reply is likely to give a deeply misleading picture to readers unfamiliar with this period.…”
Section: What Can We Know About the Roman Pandemics?mentioning
confidence: 99%